Peranan Model Pembelajaran Berbasis Etnomatematika sebagai Inovasi Pembelajaran dalam Meningkatkan Literasi Matematika - I Made Surat (Emasains : Jurnal Edukasi Matematika dan Sains, 2018)
Based on the results of PISA 2015, Indonesia is included in 10 countries with low literacy capability. The average Indonesian student score for math literacy is 375 (level 1) while the average international score is 500 (level 3). Level 1 is the lowest level of the 6 levels of mathematical literacy skills applied by PISA. Most high school students still have difficulty expressing their ideas, either in visual form, in mathematical expressions, or in words when solving math problems. Students are also afraid to present the results of their work in discussions, both in front of the class, and in their study groups, even in answering questions from teachers. It shows that the mathematical literacy of students in learning mathematics is still low. One of the learning models that is expected to improve students' mathematical literacy skills is ethnomatematics. The main purpose of this study is for the role of learning model based on ethnomatematics as learning innovation in improving mathematics literacy. Cultural-based mathematics learning (etnomatematics) is one way that can make learning mathematics more meaningful and contextual that is closely related to the cultural community. In addition, cultural-based mathematics learning will be an interesting, fun and innovative learning alternative because it allows contextual meaning based on the experience of the students as a member of a cultural society that is expected to participate in supporting the literacy movement. For the development of continuous learning of mathematics, etnomatematics can serve as a reference and a means to bridge between mathematics as a science with the socio-cultural culture of Balinese society. As a follow up of this study is the government should conduct socialization related to innovation of learning based on ethnomatematics.